Performance of gerbera cultivars under different wavelengths of solar spectrum - Mehraj, H; Taufique, T; Ona, AF; Nusrat, A; Uddin, AFM Jamal (Journal of Bangladesh Academy of Sciences, 2014)
To find out the response of potted gerbera under different light spectrum wavelengths of solarradiation was carried out. Three gerbera cultivars viz. V1 (red), V2 (pink), V3 (brick red) and seventreatments viz. L1 (full spectrum), L2 (no spectrum), L3 (cut of 380 - 750 nm wavelength), L4 (cut of620 - 750 nm wavelength), L5 (cut of 450 - 495 nm wavelength), L6 (cut of 495 - 570 nmwavelength) and L7 (cut of 570 - 590 nm wavelength) were exerted on the experiment. Among thecultivars brick red was the best one. Plants were green because they reflected 495 - 570 nmwavelengths (green band) from the visible spectrum of solar radiation. Current findings indicatedthat of 495 - 570 nm wavelengths (green band), the plants responded alike to the full spectrum. Nospectrum provided the worst result in all attributes of gerbera. Number of flower, peduncle length,peduncle diameter, flower head diameter and bending percentage were least after no spectrum in allthe treatments. All the treatments except full spectrum and of 495 - 570 nm wavelength (greenband) restricted for the entrance of the 620 - 750 nm wavelength (red band); 620 - 750 nmwavelength (red band) of light was very important for the plants. Besides, absence of 620 - 750 nmwavelengths (red band) and 450 - 495 nm wavelength (blue band) drastically hampered plantgrowth, yield and quality contributing characters. DOI: http://dx.doi.org/10.3329/jbas.v38i1.20202 Journal of Bangladesh Academy of Sciences, Vol. 38, No. 1, 27-37, 2014